Respostas

2014-05-09T14:50:35-03:00
Comparando a equação com a equação geral da circunferência.
a) x²+ y² + 18x= 0 
   x²+ y²  - 2ax - 2by +  a2 + b2 – r2 = 0 
Centro                                    Raio
-2a = 18      -2b = 0                0=a² + b² - R²
a = 18/ -2      b = 0/-2             R² = (-9)² + 0² -0
a = -9            b = 0                 R² = 81
          C(-9 0 )                         R = √81
                                             R = 9
x²+ y²= 16
x²+ y²-16=0
x²+ y²  - 2ax - 2by +  a2 + b2 – r2 = 0 
Centro                                  Raio
C(0 0)                                    -16= a² + b² - R²
                                              R² = 0² + 0² +16
                                              R = √16
                                              R = 4
  c) x²+ y²+ 4x- 10y+ 20= 0
    x²+ y²  - 2ax - 2by +  a2 + b2 – r2 = 0
Centro                                   Raio
-2a = 4        -2b = 10              20= a² + b² - R²
a = 4/-2        b = 10/-2            R² = (-2)² + (-5)² - 20
a = -2          b = -5                 R² = 4 + 25 -20
C(-2 -5)                                 R² = 9
                                            R = √9
                                            R = 3

d) x²+ y²+ 4x+ 4y- 17=0
   x²+ y²  - 2ax - 2by +  a2 + b2 – r2 = 0
Centro                                 Raio
-2a = 4      -2b = 4                -17=a² + b² - R²
a = 4/-2      b = 4/-2               R² = (-2)² + (-2)² + 17
a= -2          b = -2                  R² = 4 + 4 + 17
C(-2 -2)                                  R²= 25
                                            R= √25
                                            R = 5
1 4 1